治理與自理交織的專業發展探索－一位校長的敘說研究 The Professional Development Exploration between Governance and Self-Care The Narrative Research of A Principal - 朱麗玲 Li-Ling Chu; 郭丁熒 Ding-Ying Guo (National Changhua University of Education, 2019)
「校長」是一個學校的表徵、首長與核心人物，其一舉一動，都影響著學校的人、事、物發展，專業的校長更能引領學校前進，展現新氣象，締造校園和諧與人文氣息。故，校長的專業素養，不容忽視。本研究主要從 Foucault 的治理性觀點出發，探究一位初任校長成為一位專業校長的修為，從中找尋專業治理性的內涵以及在專業發展中自理性的發展，並嘗試以社群運作成就自己與教師的專業發展為主要目的。本研究採用敘說研究，從學校與 8 位教育人員社群運作歷程中的對話語錄、會議紀錄、正式與非正式訪談、日誌、反思札記、line 自我書寫、其他開放性資料等，進行 Foucault論點中關懷自身的傾聽、對話辯證、說真話、告解坦白、自我書寫等資料分析，並透過校內與社群成員的三角校正檢閱信實度，從中得到許多寶貴經驗。 一、專業校長的修為具備三項修煉：「動靜」的平衡力；對「人」的關懷；求「真」的本質。 二、專業治理運作內涵包含了：「知性」的內在；「感性」的外在；「靈性」的修行。 三、促使老師能「自理性」專業發展需有：善的原創性思想；教育者的引導；有規劃的 工作體驗；不以個人能力與貢獻為參照標準。 "The Principal" is the image, the chief, and the core of a school. Every move of him or her affects everyone and everything in the school. A professional principal can direct a school forward, create new perspectives and generate humane and harmonic atmosphere. Thus, the profession of a principal cannot be ignored. This study is, mainly on the of Foucault's thought of governmentality, how a new principal becomes professional and then to discover the essence of professional governmentality and the self-care professional development and to achieve the professional development through teacher's community. This study conducts a narrative approach. The data are collected from eight teachers' communication records with the school authority such as dialogue, meetings, formal and informal interviews, diary, reflection notes, line writing, other open materials, etc. and analyzed by listening, dialectical dialogue, telling the truth, confessing, self- writing of Foucault's idea of the care of the self. In addition, the triangulation is applied to test the reliability. It concludes that 1. The cultivation of a professional principal is the development of the balance between "movement" and "stillness", the care for "people", and the pursuit of the "truth". 2. The essence of professional governance is the combination of "reasonability", "intellectual", "sensibility", and "spirituality". 3. The self-care development of teachers' profession is motivated by the original idea of goodness, the educators' guidance, and the organized working experience. It is also not determined by the ability and contribution.